When nudges fail to scale: Field experimental evidence from goal setting on mobile phones - Andreas Löschel; Matthias Rodemeier; Madeline Werthschulte (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
Non-pecuniary incentives motivated by insights from psychology ("nudges") have been shown to be effective tools to change behavior in a variety of fields. An often unanswered question relevant for public policy is whether these promising interventions can be scaled up. In cooperation with a large public utility in Germany, we develop an energy savings application for mobile phones that can be used by the majority of the population. The app randomizes a goal-setting nudge prompting users to set themselves energy consumption targets. The roll-out of the app is promoted by a mass-marketing campaign and large financial incentives. Results document low demand for the energy app in the general population and a tightly estimated null effect of the nudge on electricity consumption among app users. A likely mechanism of the null effect is unfavorable self-selection into the app: users are characterized by an already low baseline energy consumption and exhibit none of the behavioral biases that typically explain why goal setting affects behavior. We also find that the nudge significantly decreases the likelihood to use the app over time. Structural estimates imply that the average user is willing to pay 7.41 EUR to avoid the nudge and the intervention would yield substantial welfare losses if implemented nationwide.
Keywords: C93; D91; Q49; 330; nudging; goal setting; scalability; field experiments; energy; behavioral welfare economics; mobile phones